Viagens de Mário de Andrade: a construção cultural do Brasil - Santos, Marcelo Burgos Pimentel dos (2012)
This thesis examines the relationship between literature and social sciences in two crucial aspects: culture and politics. We analyzed the importance of two ethnographic travels named O Turista Aprendiz, in the work and political career of Mario de Andrade. These journeys, occurred in 1927 and 1928-9, were important for rousing the contact with inside Brazil that the modernist writer have always looked for. One of the main issues of the aesthetic project of Mario de Andrade was "to look inside of Brazil" searching for its true origins. In our view, this look was responsible for developing two other strands on Andrade's work since reverberated in a project Na Pancada do Ganzá that can be explained, at first, as its contribution to the Brazilian social thought in seeking an interpretation of Brazilianness from the cultural field. Also echoed in political actions, in a institutional way, when he took over and led the Department of Culture of the Municipality of São Paulo. For this, we observe the actions of Mario de Andrade, from three basic axes: the literary man, the researcher man and politician man. All these strands establish links among themselves to help the measurement of the contribution that Andrade gave to the Social Sciences and to understand Brazil. In addition to the links between these strands, we noted how collaboration and networking are important tools in Mário de Andrade's work in both its aesthetic and ideological conceptions